Exploring the effectiveness of the teaching strategies that technology teachers apply to teach the design process - Sephoto, Sibongile Annah Khethiwe (My University, 2018)
Technology education was introduced in the South African curriculum by the Department of Basic Education with the intention of developing learners’ design skills while using the design process. Since the introduction of technology education, the South African curriculum has undergone a series of curriculum changes. Teachers were introduced to Outcomes-Based Education (OBE), the Revised National Curriculum Statement (RNCS), the National Curriculum Statement (NCS) and now the Curriculum and Assessment Policy Statement (CAPS). These changes compelled South African teachers to shift from a teacher-centred approach to that of a learner-centred approach. In the RNCS, the design process was presented as a linear process, whereas in the CAPS document, the design process has been represented as non-linear. This change has led to uncertainties amongst technology teachers on how to teach the design process. The purpose of this study was to explore the effectiveness of the teaching strategies that technology teachers apply when teaching the design process. The CAPS document for technology stipulates that technology should give learners an opportunity to develop and apply specific design skills to solve technological problems in real situations. To solve such problems, learners should be exposed to a problem and then engage in a systematic process that allows them to develop solutions to the problem. The theoretical framework used in this study was based on social constructivism. This theory was used based on the fact that it describes how learning occurs and puts emphasis on how learners construct their own understanding in a social context. This social constructivism was linked to the design process skills required to demonstrate the way in which the teaching and learning of the design process could be directed. The design process is seen as the backbone of technology and should be used to teach technology, it seems that teachers are struggling to use the design process in teaching technology. The literature revealed that teachers’ lack of knowledge in technology has an effect on how they use various teaching strategies to teach the design process. This is challenging and a reason for unease, therefore this study needed to explore this problem. The study engaged in qualitative research using a case study design. Purposive sampling was used to select the participants, who comprised technology teachers who obtained anAdvanced Certificate in Education majoring in technology with at least six years of experience in teaching technology. Data were collected using semi-structured interviews and observations, and were analysed using Shulman’s Pedagogical Content Knowledge. The study revealed that only in exceptional cases were technology teachers using problem-solving to teach the design process. It was also revealed that technology teachers have difficulties with regard to PCK. The sampled teachers were also unable to support learners to acquire design skills such as investigation, designing, making, evaluation and communication. The observations indicated that the participants did not engage with the design process as set out in the CAPS document for technology. The implication of this study is that understanding the content and how to teach it is essential in teaching and learning situations. There should be ongoing professional development programmes to assist technology teachers. This study recommends that there should be repeated in-service training of technology teachers to address the issue of concern in teaching the design process. Teachers should be encouraged to attend such in-service training. The in-service training should also focus on teaching technology using the design process. Furthermore, technology teachers should encourage effective group-work in problem solving so that every member of the group has a role to play.
Thesis (M.Ed.) -- University of Limpopo, 2018
Keywords: Design process; Social Constructivism; Problem-solving; Educational technology.; Education-Curricula.